Reducing wall-clock time for the computation of all efficient extreme points in multiple objective linear programming - Piercy, Craig A.; Steuer, Ralph E. (European journal of operational research, 2019)
•Exploits the objective function structure of a multiple objective linear program.•Shows methods for decomposing the criterion cone.•Allows for the computation of all efficient extreme points by distributed processing.•Computational experiments show typical time savings running from 40 to 70%. This paper describes an approach for markedly reducing the time required to obtain all efficient extreme points of a multiple objective linear program (MOLP) with three objectives. The approach is particularly useful when working with such MOLPs possessing large numbers of efficient extreme points. By subdividing the criterion cone into sub-cones, the paper shows how the task of computing all efficient extreme points can be broken down into parts so that the parts can be solved concurrently, thus allowing all efficient extreme points to be computed in much reduced elapsed time. The paper investigates several schemes for conducting this task and reports on a volume of computational experience.